Effects of physical stimuli applied via substrate/scaffold on in-vitro culture of mesenchymal stem cells and neurons - Xu, Qinwei (2017)
Interactions between cells and the microenvironment have been demonstrated to be key factors in cell behavior regulation. Among the different cues provided by the microenvironment, the physical cues from the microenvironment are emerging at a rapid pace and have attracted a lot of attention. However, the studies in this area have not yet been comprehensive, and many phenomena and mechanisms have still not been completely clarified. For example, the effects caused by physical stimuli could be complex considering other factors, such as culture time, three-dimensional (3D) structure of scaffolds, etc. This Ph.D. project was proposed to obtain a better understanding of cell-microenvironment interactions with physical stimuli, and three sub-projects were conducted specifically for this purpose. In the first part, the mechanical properties of human mesenchymal stem cells (hMSCs) were found to be influenced by both the mechanical properties of the substrates that they adhered to and the culture time. The results showed that cells well aligned their mechanical properties according to the substrate stiffness and cell moduli as functions of time displayed non-monotonic trend. This project proved the concept of regulating cell modulus through modifying cell growth substrates and culture time. In the second part, the effect of dynamic loading on hMSCs in a 3D scaffold was investigated. A 3D nanofibrous scaffold (3D-CNFs) was fabricated using a novel method for creating a 3D cell culture. These conductive PPy-coated 3D-NFs (3D-CNFs) showed super-elastic properties, which supported the dynamic cell culture of hMSCs. It was found that cell penetration and adhesion were supported by 3D-CNFs. In the condition of dynamic compressive loading, the morphology and collagen expression of hMSCs in 3D-CNFs were changed. It provided a new way to build a dynamic 3D cell culture to studying cell-microenvironment interactions. The last part studied the effect of electrical stimulation (ES) applied on neurons and glial cells in the 3D-CNFs. It was conducted to address the combined effect of 3D-CNFs scaffolds and ES on cell cultures. 3D-CNFs with 3D structures successfully supported the 3D culture of cortical cells. ES changed the morphology and distribution of cells. ES also increased the proliferation of cortical cells in the 3D-CNFs significantly. Furthermore, the maturation of neurons in 3D-CNFs was promoted significantly by ES compared to unstimulated neurons starting from the first day of culture. These combined effects indicated that ES and 3D-CNF have broad applications in neural engineering, such as implantation and biofunctional in vitro models.